Les secrétaires régionaux du Parti communiste français (1934-1939) Du tournant antifasciste à l'interdiction du Parti - Manessis, Dimitri (Histoires, 2022)
By focusing on the trajectories of 187 men and women activists of the French Communist Party who played a pivotal role in the organisation as regional secretaries, this work reflects on the social history of politics based on an abundant archival corpus (internal and police archives, activist memories, newspapers, etc.). It renews the approach to studying communism in France by filling an historiographic void. Several studies have examined the highest leadership circles of the French Communist Party, but what is the history of the intermediary leaders? Alternating between the local and international levels, but also between the bottom and top levels of the organisation, this work is chronologically framed by the era of the Popular Front, a period of profound transformation of the French Communist Party. From the anti-fascist turning point in 1934 to the prohibition of the party in 1939, not to mention the strikes in 1936 and the Spanish Civil War, how did these communists live and fight, having become ambassadors of a mass party seeking respectability and balancing central injunctions with expectations among the base?